Persepsi Mahasiswa Terhadap Maraknya Normalisasi Hubungan Sesama Jenis Dalam Pandangan Islam - Selviana R. D; Nofitri R.; Karina D. Lestari; Sherly A. Rimadhani; Arzyntha N.A.P. Wahyuni; Saifuddin Z (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
The topic of LGBT and homosexuality seems to be endlessly discussed. This is due to several scientific fields such as health, psychology, Islamic law, and other related fields that can significantly influence the decision-making process related to these issues. The problems include positioning LGBT or homosexual relationships as nature or nurture, innate or socially constructed, genetic or deviant, normal or abnormal, and so on. This abnormal behavior creates misunderstandings about sex in this group. This shows that people who maintain LGBT or homosexual relationships are unable to reconcile their desires and principles of life. Therefore, this article aims to identify the perceptions and efforts of Islamic religious education students towards the increasing normalization of LGBT in Indonesia. It also aims to educate the public about the understanding, meaning, and law of LGBT in Islam. The research method used is qualitative and is an approach or survey to examine and understand the main symptoms. To understand the main symptoms, researchers conducted interviews with respondents, asking several more general questions. After conducting interviews, the researchers initially obtained conflicting results. Students' perceptions of LGBT were contradictory. Second, PAI students do not agree that LGBT is normalized in Indonesia, either officially (legalized by the government) or unofficially (considered normal by society). The third effort of PAI students in minimizing LGBT in Indonesia is by providing education to the community directly or indirectly.